Motor DC PID System Regulator for Mini Conveyor Drive Based-on Matlab - Latif, Abdul; Zuhri Arfianto, Afif; Agus Widodo, Hendro; Rahim, Robbi; T.Helmy, Elsayed (Journal of Robotics and Control (JRC), 2020)
The goal of the research was to develop a Proportional Integral Derivative (PID) control DC motor system as a Matlab-based driver mini conveyor to discover how to regulate speed on an actual mini conveyor where certain factors that impact the research are not considered 0. The hardware configuration of the mini conveyor used hollow steel as a frame and two copies of the roller belt for the stretch belt conveyor. The PID control system used an empirical approach to get the DC motor's response system to determine the best fit of proportional gain, integral gain and derivative gain, and then implement those PID control systems using Matlab and Arduino as the tools for data acquisition. The speed sensor (Rotary Encoder) was mounted on the roller belt to accurately gain read speed. This sensor will submit data on every increasing in PWM to accurately measure the speed and control speed at the same time, based on the set points. The consequence of this work was the proportional gain values = 0.94624747, the Integral gain = 51.4023958 and the derivative gain = 0.01941504. The PID control, designed to monitor the response of motor DC speed on this research, had successfully reached set point value and decreased steady state error from 47.16 percent to 1.015188 percent (unloaded) and 2.2020751 percent (loaded) on the real response device.